Aplicabilidade do Google Classroom na formação dos docentes do município de Igaci-Alagoas - Lima, Ivonaldo Pereira de (2022)
Teacher training has taken up space in major debates in universities and events in the field of education, as it is still a major challenge for Brazilian education. When it comes to teacher training, with the insertion of technologies as a motivator in learning, the challenge is even greater. It is necessary that teaching networks are attentive to the real needs of teachers, so that they can have study practices that are coherent with the demands that arise daily. Within this context, this thesis had as main objective to analyze the use of Google Classroom as a virtual environment in the training of teachers in the municipality of Igaci - Alagoas and, as specific objectives: to know actions of teaching practice that can be re-signified through training; to identify the challenges of teachers who lack training to use Digital Information and Communication Technologies (TDIC) in their own training; implement the use of Google Classroom as a support tool for teacher training aimed at improving study and teaching practices. To this end, we seek to investigate how Google Classroom contributes to teacher training. Thus, the methodology applied in this study sought to develop a research characterized, in terms of approach, as a qualitative research, allowing a better understanding of the context of the object of study. With regard to the objectives, it was exploratory and descriptive, in the procedures of the participant research, data collection through a profile characterization questionnaire applied, through google forms, interviews and participant observation with 20 (twenty) Portuguese Language (LP) teachers, under the care of a pedagogical technician appointed by the Municipal Department of Education (SEMED). The sample was intentional and not probabilistic. Also, to compose the state of the art, we carried out bibliographic research in databases. The collected data were analyzed from the perspective of content analysis procedures, based on Bardin (2011). In theoretical terms, studies point out that technology by itself does not change training practices. The issue goes beyond whether or not to use technology, passing through public policies to encourage teachers and structural conditions of teaching networks and schools. The results of the empirical research highlighted the need for the Municipal Department of Education of Igaci and its schools to rethink the methodology of practice developed in the training of teachers, in a way that contemplates studies and meetings regardless of space and time. Therefore, it is necessary to provide teachers with training moments in which, even outside the group, study and interaction continue, as well as the use of Google Classroom, since, thanks to its potential, it will be able to strengthen the dynamics of this on-site training.